2010
DOI: 10.1021/jp911293e
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Platinum Films Deposited by Polyol Reduction of a Platinum Precursor and Their Application as Counter Electrode of Dye-Sensitized Solar Cells

Abstract: Platinum precursors such as H 2 PtCl 6 can be reduced to platinum (Pt) by polyols at temperatures below 200 °C. This method was developed to deposit nanostructured Pt films on various substrates through a solution process. High-quality Pt films with good adhesion to substrate were obtained on substrates like conducting polymer films, indium tin oxide (ITO), and polyimide by dropping a solution of H 2 PtCl 6 in ethylene glycol (EG). Two types of Pt structures, that is, dense and porous Pt structures, were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 53 publications
2
55
0
Order By: Relevance
“…Previous research has shown the use of alcohols as active platinum reductants in the presence of polymers. 52,53 FTIR analyses further showed that these weak carbonyl-platinum interactions could be dissociated by acids such as the electrolytes used for ORR since simple rinsing of the PEG-Pt particles in 0.5M H 2 SO 4 caused the polymers to wash off (Fig. 3A, S2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown the use of alcohols as active platinum reductants in the presence of polymers. 52,53 FTIR analyses further showed that these weak carbonyl-platinum interactions could be dissociated by acids such as the electrolytes used for ORR since simple rinsing of the PEG-Pt particles in 0.5M H 2 SO 4 caused the polymers to wash off (Fig. 3A, S2).…”
Section: Resultsmentioning
confidence: 99%
“…Similar synthesis procedure as reported by Sun et al was used (16). All substrates were cleaned using the procedure described earlier.…”
Section: Polyol Processmentioning
confidence: 99%
“…Under such a thermal treatment, the shapes and the sizes of the nanostructures are difficult to control because of their deformation or aggregation at high temperatures. Although Cho et al 23,24 reported a polyol reduction to prepare Pt CEs for DSSCs at temperatures of 160-180 1C, it is difficult to prepare the thin layer of Pt nanostructures with a uniform morphology and size distribution on TCO at temperatures near 295 K, in particular, to obtain the advantages of excellent electrocatalytic function, large active surface area and effective adhesion to the substrate. As highlighted in Figure 1, in the present work, we demonstrate a feasible strategy for preparing self-assembled Pt monolayers (SAM-Pt) on the surface of TCO in two steps without adding a surfactant or protective agent; thus, the postheating step is avoided.…”
Section: Introductionmentioning
confidence: 99%